The effect of aortic stenosis on elderly hip fracture outcomes: A case control study. Issue 2 (February 2016) - Keswani, Aakash; Lovy, Andrew; Khalid, Mian; Blaufarb, Ira; Moucha, Calin; Forsh, David; Chen, Darwin
Abstract: Introduction: Aortic stenosis (AS) is an established predictor of perioperative complications following both cardiac and non-cardiac surgery. The purpose of this study was to evaluate the risk of mortality and perioperative complications among surgically treated hip fractures in elderly patients with moderate or severe AS compared to those without AS (negative controls). Materials and methods: A retrospective case-controlled review (1:2) of elderly (≥65 years) surgically treated hip fractures from 2011 to 2015 with moderate/severe AS (according to American Heart Association criteria) was conducted. Postoperative complication rates, 30 days and 1 year mortality were reviewed. Results: Moderate/severe AS was identified in 65 hip fracture cases and compared to 129 negative controls. AS cases were significantly older with higher rates of coronary artery disease and atrial fibrillation ( p  < 0.05). Rates of any 30-day perioperative complication (74% vs. 37%, p  < 0.001) and severe non-cardiac 30-day perioperative complication (52% vs. 26%, p  = 0.002) were significantly higher among AS cases compared to controls. Kaplan Meier estimates of 30-day mortality (14.7% vs. 4.2%, p  < 0.001) and 1-year mortality (46.8% vs. 14.1%, p  < 0.001) were significantly higher in AS cases compared to controls. Multivariate analysis of severe 30-day postoperative complications identified moderate/severe AS (OR 4.02, p  = 0.001), pulmonary disease (OR 7.36, p  = 0.002) and renal disease (OR 3.27, p  = 0.04) as independent predictors. Moderate/severe AS (OR 3.38, p  = 0.03), atrial fibrillation (OR 3.73, p  = 0.03) and renal disease (OR 4.44, p  = 0.02) were independent predictors of 30-day mortality. Moderate/severe AS (OR 5.79, p  < 0.001) and renal disease (OR 3.39, p  = 0.02) were independent predictors of 1-year mortality. Conclusion: Aortic stenosis is associated with a significantly increased risk of perioperative complications, 30-day mortality and 1-year mortality in elderly patients undergoing surgical treatment of hip fractures.